Impact of MicroRNAs in Interaction With Environmental Factors on Autism Spectrum Disorder: An Exploratory Pilot Study - Cui, LiHua; Du, WenRan; Xu, Ning; Dong, JingYi; Xia, BingJie; Ma, JingYi; Yan, RuoTong; Wang, LanYing; Feng, FuMin (Frontiers in Psychiatry, 2021)
Background: This study aimed to explore the main effects of environmental risk factors as well as their interaction effects with miRNA on the risk of autism spectrum disorder (ASD). Methods: 159 ASD children (ASD group) and 159 healthy children (control group), aged 2-6 years, were included in this study. ASD diagnoses were based on DSM-5 criteria. The extensive medical and demographic characterization of the two groups were recorded. And microRNAs (miRNAs) in serum were detected by qRT-PCR. Results: Comparing to control group, ASD group had significant higher rates of maternal stress during pregnancy (p<0.001), maternal drinking during pregnancy (p=0.006), threatened abortion (p=0.011), pregnancy-induced hypertension (p=0.032), gestational diabetes (p=0.039), maternal anemia during pregnancy (p<0.001), umbilical cord knot (p<0.001), neonatal jaundice (p<0.001), family psychiatric history (p=0.001), and much lower birth weight (p=0.012). Furthermore, ASD group had much lower expression levels of hsa-miR-181b-5p (p<0.001) and hsa-miR-320a (p<0.001), and significant higher levels of hsa-miR-19b-3p (p<0.001). The interactions of hsa-miR-320a and maternal stress during pregnancy (OR=39.42, p<0.001), hsa-miR-19b-3p and neonatal jaundice (OR=2.44, p<0.001), hsa-miR-181b-5p and family psychiatric history (OR=8.65, p=0.001) could increase ASD risk. Conclusions: The dysregulation of hsa-miR-181b-5p, hsa-miR-320a and hsa-miR-19b-3p could interact with environmental factors, such as maternal stress during pregnancy, neonatal jaundice and family psychiatric history, to impact the risk of ASD.